2018
DOI: 10.1096/fj.201800105r
|View full text |Cite
|
Sign up to set email alerts
|

Sustained spatiotemporal release of TGF‐β1 confers enhanced very early chondrogenic differentiation during osteochondral repair in specific topographic patterns

Abstract: The continuous presence of TGF-β is critically important to induce effective chondrogenesis. To investigate chondrogenesis in a cartilage defect, we tested the hypothesis that the implantation of TGF-β1-releasing scaffolds improves very early cartilage repair in vivo. Spatiotemporal controlled release of TGF-β1 was achieved from multiblock scaffolds that were implanted in osteochondral defects in the medial femoral condyles of adult minipigs. We observed a sustained presence of TGF-β1 at 4 wk in vivo, which si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The minimal sample size of 8 was calculated as previously described. [31,56] Healthy, skeletally mature female Aachener minipigs (age 18-22 months, average body weight (BW): 42.75 ± 6.54 kg; Gerd Heinrichs, Heinsberg, Germany) were fed by standard diet and received water ad libitum. After 12 h fasting, sedation was induced with an intramuscular injection of 30 mg ketamin per animal (Ketanest S, Pfizer, Berlin, Germany), 2 mg xylazine per animal (Rompun, Bayer, Leverkusen, Germany), and 1 mg atropine per animal (B. Braun, Melsungen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The minimal sample size of 8 was calculated as previously described. [31,56] Healthy, skeletally mature female Aachener minipigs (age 18-22 months, average body weight (BW): 42.75 ± 6.54 kg; Gerd Heinrichs, Heinsberg, Germany) were fed by standard diet and received water ad libitum. After 12 h fasting, sedation was induced with an intramuscular injection of 30 mg ketamin per animal (Ketanest S, Pfizer, Berlin, Germany), 2 mg xylazine per animal (Rompun, Bayer, Leverkusen, Germany), and 1 mg atropine per animal (B. Braun, Melsungen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, bioactive agents are well protected once encapsulated in liposomes from the external harsh in vivo environment [ 10 , 11 , 12 ]. This could solve the short half-life, low stability and poor penetration into cartilage of transforming growth factor (TGF)-β1, which has shown positive effects on chondrocytes [ 13 , 14 , 15 , 16 ] by binding to their receptors and activating signaling pathways among which the best known are extracellular signal-regulated kinase (ERK), p38-mitogen-activated protein kinase (p38-MAPK) and Smad [ 17 , 18 , 19 ]. Indeed, TGF-β1 is known to retain chondrocyte articular phenotype by inducing the genes coding for Col 2, ACAN and Sox-9 [ 16 , 20 ], as well as the release of inorganic pyrophosphate (PPi) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that undifferentiated MSCs that migrated from the bone marrow into the defect 54 represent the major reparative cell population, as reported in a previous study 2 (although that work did not specifically assess their source), whereas MSCs of synovial or other origins could contribute. 2,28 Although Correa et al 7 reported that FGF-2 is an early activator of the chondrogenic machinery in MSCs, those investigators also identified accelerated hypertrophic changes after FGF-2 exposure in vitro. A hypertrophic phenotype reflects degeneration and therefore is undesirable for chondral repair.…”
Section: Discussionmentioning
confidence: 99%